1995
DOI: 10.1200/jco.1995.13.8.1880
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent cisplatin/etoposide plus chest radiotherapy followed by surgery for stages IIIA (N2) and IIIB non-small-cell lung cancer: mature results of Southwest Oncology Group phase II study 8805.

Abstract: This trimodality approach was feasible in this Southwest Oncology Group (SWOG) study, with an encouraging 26% 3-year survival rate. An Intergroup study is currently being conducted to determine whether surgery adds more to the risk or to the benefit of chemoRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
495
4
13

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 805 publications
(548 citation statements)
references
References 43 publications
36
495
4
13
Order By: Relevance
“…In agreement with these results, we found that chemotherapy activity at the primary tumour, mediastinal downstaging and complete tumour resection (with a negative uppermost mediastinal lymph node) were strongly associated with improved OS and EFS, and reduced risk of local and distant relapse. Our identification of nodal downstaging from N2 to N1 and/or N0 as a powerful prognostic marker is consistent with findings by Albain et al (1995), who found that mediastinal nodal downstaging (to N0) was predictive of improved survival in IIIA/IIIB patients, although inclusion of preoperative radiotherapy makes it difficult to evaluate the independent effect of neoadjuvant chemotherapy on this outcome. Similarly, in a retrospective analysis of 103 patients who underwent neoadjuvant therapy and resection for stage IIIA pN2 disease, downstaging to N0 was associated with improved 5-year survival compared with patients who were N2 or N1 after chemotherapy (no difference in survival was seen between N2 and N1 patients in this analysis) (Bueno et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with these results, we found that chemotherapy activity at the primary tumour, mediastinal downstaging and complete tumour resection (with a negative uppermost mediastinal lymph node) were strongly associated with improved OS and EFS, and reduced risk of local and distant relapse. Our identification of nodal downstaging from N2 to N1 and/or N0 as a powerful prognostic marker is consistent with findings by Albain et al (1995), who found that mediastinal nodal downstaging (to N0) was predictive of improved survival in IIIA/IIIB patients, although inclusion of preoperative radiotherapy makes it difficult to evaluate the independent effect of neoadjuvant chemotherapy on this outcome. Similarly, in a retrospective analysis of 103 patients who underwent neoadjuvant therapy and resection for stage IIIA pN2 disease, downstaging to N0 was associated with improved 5-year survival compared with patients who were N2 or N1 after chemotherapy (no difference in survival was seen between N2 and N1 patients in this analysis) (Bueno et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…In several studies, and most notably in the recently reported EORTC trial, patients were excluded from attempted surgical resection in the absence of a response to induction therapy. In fact, patients with 'clinically stable disease' following neoadjuvant therapy not uncommonly have major pathological response at the time of surgery, as has been observed previously (Albain et al, 1995) and in the present trial. Clearly, better methods of assessing response after preoperative therapy are needed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The difference in toxicity was due to the different dose and schedule used in Van Zandwijk et al (2000) study ( therapy in inoperable stage III NSCLC patients. (Albain et al, 1995). The response rate was 59%.…”
Section: Discussionmentioning
confidence: 93%